2022
DOI: 10.1093/jamiaopen/ooac079
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth care before and during COVID-19: trends and quality in a large health system

Abstract: Background COVID-19 accelerated telehealth use to ensure care delivery, but there is limited data on the patient perspective. Objective To examine telehealth visit uptake before and during COVID-19 and correlates of patient satisfaction and interest in future telehealth visits. Design Cross-sectional observational study between October 2019 and April 2020. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…At a system or institutional-level consideration, also finding opportunities to evaluate a patients’ technology/internet access and internet quality as part of the scheduling process and providing technology onboarding and support as needed. 45 , 46 …”
Section: Discussionmentioning
confidence: 99%
“…At a system or institutional-level consideration, also finding opportunities to evaluate a patients’ technology/internet access and internet quality as part of the scheduling process and providing technology onboarding and support as needed. 45 , 46 …”
Section: Discussionmentioning
confidence: 99%
“…The authors reported that teleconsultation was feasible for provision of ophthalmic services during the lockdown (17). In a study by Luna et al (2022), the majority of patients were content with the ease of contact, video quality and the guidance provided by doctors. The authors suggested that the standard of telehealth delivery platforms and patient instructions should be raised in order to maintain interest in future telehealth use and enhance the patient experience (18).…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Luna et al (2022), the majority of patients were content with the ease of contact, video quality and the guidance provided by doctors. The authors suggested that the standard of telehealth delivery platforms and patient instructions should be raised in order to maintain interest in future telehealth use and enhance the patient experience (18). In a similar study done by Alromaihi et al (2023), evaluation of patient satisfaction to teleconsultation services showed that around 89% of the patients were satisfied with the quality of teleconsultation (19) With high dependence on internet and mobile phone, technical glitches are likely during teleconsultation.…”
Section: Discussionmentioning
confidence: 99%
“…Research examining patients' experiences of telemedicine during the pandemic indicate that di culties with using patient portals and poor video quality could have impacted quality of care for telemedicine users with diabetes and/or hypertension. (35) To improve the reach of screening efforts, clinic-community pharmacy partnerships and other outreach methods may also be needed to consistently monitor HbA1c and BP during times when in-person care options are limited. (14)(15)(16)36) Our results should be considered with some limitations.…”
Section: Discussionmentioning
confidence: 99%